Management Factors and Conditions of Higher Education Students Professional Mobility Formation - Mishchenko, Vladimir A.; Belova, Larisa Ð.; Frolova, Elena V.; Torkunova, Julia V.; Dudov, Aleksandr V.; Galiyev, Radik M.; Palyanov, Mikhail P.; Tenyunina, Inna A. (International Review of Management and Marketing, 2016)
In contemporary terms of globalization and modernization of higher professional education the tasks of those specialists' training are relevant, which not only can easily learn, but also adapt quickly to changing conditions and to the content of their professional activities. In this context, this article is aimed at the characteristics' identifying of students' professional mobility formation. The leading methods in the study of this problem are diagnostic, observational, proxy-metrical methods, study and generalization of the advanced pedagogical experience, methods of data statistical treatment using the package SPSS. The article reveals the students' attitude to the phenomenon of professional mobility; the basic reasons that may lead to occupation or specialty change by the graduates after university graduation are studied; educational and management conditions are offered contributing to the efficiency of the process; dynamics of students' professional mobility formation during their study at the university is defined. The contents of this article can be useful for faculty members of higher educational institutions in the selection and structuring of learning content and the implementation of career guidance with graduates of schools and colleges. Keywords: professional mobility, students, high school, management, factors, conditions. JEL Classifications: A23, I23, I26